Evaluation of hepatitis B virus replication and proteomic analysis of HepG2.2.15 cell line after cyclosporine A treatment - Xie Hai-yang; Xia Wei-liang; Zhang Chun-chao; Wu Li-ming; Ji Hao-feng; Cheng Yu; Zheng Shu-sen (Acta Pharmacologica Sinica, 2016)
Aim: The effect of cyclosporine A (CsA) on hepatitis B virus (HBV) replication was investigated, and proteomics expression differentiation after CsA treatment was studied in order to provide clues to explore the effect of CsA on HBV replication. Methods: Methyl thiazolyl tetrazolium (MTT) assay was used to evaluate the cytotoxicity of CsA. The HBV replication level in the HBV genomic DNA transfected HepG2.2.15 cell line was determined by an ELISA analysis of hepatitis B surface antigens (HBsAg) and Hepatitis B e antigens (HBeAg) in culture supernatant, while the intracellular HBV DNA replication level was analyzed by slot blot hybridization. Two-dimensional electrophoresis was used to investigate the alteration of protein expression in HepG2.2.15 after CsA treatment in vitro. The differentially-expressed proteins were identified by Matrix-assisted laser desorption/ionization-time of flight mass spectrometry combined with an online database search. Results: CsA was able to inhibit the expression of HBsAg, HBeAg, and HBV DNA replication in vitro in a dose-dependent manner. A proteomics analysis indicated that the expression of 17 proteins changed significantly in the CsA treatment group compared to the control group. Eleven of the 17 proteins were identified, including the overexpression of eukaryotic translation initiation factors (eIF) 3k, otubain 1, 14.3.3 protein, eIF2-1α, eIF5A, and the tyrosine 3/tryptophan 5-mono-oxygenase activation protein in CsA-treated HepG2.2.15 cells. The downregulation of the ferritin light subunit, erythrocyte cytosolic protein of 51 kDa (ECP-51), stathmin 1/oncoprotein, adenine phosphoribosyl-transferase, and the position of a tumor protein, translationally-controlled 1, was shifted, suggesting it had undergone posttranslational modifications. Conclusion: Our study identified the inhibitory effect of CsA on HBV replication, and found that a group of proteins may be responsible for this inhibitory effect.